2010
DOI: 10.1097/brs.0b013e3181b4af34
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Main Thoracic Adolescent Idiopathic Scoliosis Using Pedicle Screw Instrumentation

Abstract: Pedicle screw constructs provided excellent coronal correction of thoracic idiopathic scoliosis, however, this was at the expense of sagittal contour. Bilateral segmental pedicle screw fixation did not improve curve correction compared with unilateral or alternate segmental fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
70
3
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(83 citation statements)
references
References 21 publications
8
70
3
2
Order By: Relevance
“…This improvement in thoracic kyphosis confirms previous results on the use of the UC for both AIS and neurologic scoliosis [13,16,20], and contrasts with a large body of evidence suggesting that conventional all-pedicle screw constructs tend to worsen flatness of the thoracic spine in AIS [3,4,7,8,[28][29][30][31][32][33] unless rod derotation is the predominant means used to correct coronal deformity (see Table 1) [6,[34][35][36][37]. Based upon a retrospective study of patients with Lenke type 1 AIS treated with all-pedicle screw instrumentation, Quan and Gibson recently concluded that the greater the coronal plane correction achieved with pedicle-screw constructs, the greater the loss of thoracic kyphosis [33]. The authors of a large multicenter analysis of patients with Lenke type 1 AIS surgically treated by a selective thoracic fusion have recommended techniques that lengthen the posterior column in order to maintain or increase thoracic kyphosis [31].…”
Section: Discussionsupporting
confidence: 83%
“…This improvement in thoracic kyphosis confirms previous results on the use of the UC for both AIS and neurologic scoliosis [13,16,20], and contrasts with a large body of evidence suggesting that conventional all-pedicle screw constructs tend to worsen flatness of the thoracic spine in AIS [3,4,7,8,[28][29][30][31][32][33] unless rod derotation is the predominant means used to correct coronal deformity (see Table 1) [6,[34][35][36][37]. Based upon a retrospective study of patients with Lenke type 1 AIS treated with all-pedicle screw instrumentation, Quan and Gibson recently concluded that the greater the coronal plane correction achieved with pedicle-screw constructs, the greater the loss of thoracic kyphosis [33]. The authors of a large multicenter analysis of patients with Lenke type 1 AIS surgically treated by a selective thoracic fusion have recommended techniques that lengthen the posterior column in order to maintain or increase thoracic kyphosis [31].…”
Section: Discussionsupporting
confidence: 83%
“…A recent prospective cohort study with 10-year follow-up conducted by Min et al [44] has shown good correction with a pedicle screw implant density of 50 %. High implant density has not shown improvement in patient reported outcomes [38][39][40][41][42][43][44] or cosmesis [39], and has contributed to less thoracic kyphosis [38,40,41], and high costs [42,45]. In contrast to what might be expected, it was shown through a finite element analysis and computational study that high implant density does not improve the distribution of forces and correction [46,47].…”
Section: Supporting Empirical Evidencementioning
confidence: 95%
“…Some studies have shown slightly larger radiographic correction with high implant density [38][39][40], while others have shown no correlation between implant density and curve correction [41][42][43]. A recent prospective cohort study with 10-year follow-up conducted by Min et al [44] has shown good correction with a pedicle screw implant density of 50 %.…”
Section: Supporting Empirical Evidencementioning
confidence: 99%
“…Quan et al [15] also documented a significant correlation between reduced sagittal kyphosis and the magnitude of coronal Cobb angle correction in 49 consecutive patients with Lenke 1 main thoracic AIS who underwent singlestage posterior correction and instrumented spinal fusion with pedicle screw fixation. In contrast, Clement et al [31] documented a mean gain of 14°of thoracic kyphosis with pedicle screw instrumentation in patients with severe preoperative hypokyphosis.…”
Section: Discussionmentioning
confidence: 92%
“…Several reports have demonstrated that pedicle screws are superior for correcting scoliosis, in terms of the mean absolute degrees and percentage of curve correction, in comparison with posterior hook-and-wire or hybrid constructs [9][10][11]. Among the several surgical techniques available, pedicle screw instrumentation is considered to be reliable and safe [12][13][14], but clinical trials have reported a lordogenic effect with this form of posterior instrumentation [15][16][17].…”
Section: Introductionmentioning
confidence: 99%